Gender Difference in Attitudes of Learners Towards Online Learning at Higher Education of Bangladesh - Mia, Md Nahid (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
Online learning has created a new window in today’s education system. It is an entirely new experience in the education system of Bangladesh. As a result, the pupils, the tutors and the education administration face some challenges adjusting to the new learning mode. The main objective of this study was to compare the attitudes of learners studying at the different programs of the National University central campus by basing on the gender issue regarding online learning. In this study, five independent factors were identified through a literature review that influences the successful execution of online learning. It is a quantitative study where the sample size was 141, which was found by applying the formula of Yamane (1973). A stratified sampling technique was used as the population is not homogeneous. A pilot study has been conducted with 52 responses to test the validity and reliability of the factors. Two factors were excluded from over twenty-six elements through this analysis. Different descriptive statistical tools have been used to analyze the primary data by using the SPSS software version 23. The study founds no gap exists between the responses of male and female learners except for the factor of students’ competency level on digital learning technology, the supportive environment for online learning and online assessment. The output of the study also claims that the tutors’ and the academic administration’s support is significant for the successful execution of online learning. The main limitation of this study is that it ignores the educational programs of NU-affiliated campuses, which does not represent the complete scenario of NU. In this regard, further analysis can be conducted to get a more effective result. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p.1-21